A preparation process of a concrete crack self-healing repair agent and concrete material thereof
By preparing silane coupling agent modification and repair agent containing γ-C2S, MgO and graphene oxide, the problem of difficult prevention and repair of microcracks in concrete structures is solved, and the self-healing and repair of concrete structures is achieved, and its mechanical properties are improved. and waterproof and impermeable properties.
Patent Information
- Application Number
- CN202411915766.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The prior art is difficult to effectively prevent and repair microcracks in concrete structures, especially those that are not easily found inside, resulting in a decrease in the mechanical properties and waterproof and permeability of concrete structures.
Prepare a concrete crack self-healing repair agent, and use graphene oxide (GO) to disperse graphene oxide (GO) in an aqueous solution containing saturated Mg2+ source, mix γ-C2S and pretreatment solution to form a γ-C2S@MgO@GO structure and use Modified by silane coupling agent, forming a concrete crack self-healing repair agent modified by silane coupling agent (γ-C2S@MgO@GO).
This repairing agent can not only reduce cracks caused by volume shrinkage during the preparation stage of the concrete structure, but also automatically repair the generated cracks during service, reducing the adverse effects on the mechanical properties and waterproof and permeability of the concrete structure.
Smart Images

Figure CN119330627B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete material preparation, and in particular to a preparation process of a concrete crack self-healing repair agent and a concrete material thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Micro cracks will inevitably appear inside concrete structures during the manufacturing stage and in the service process, including cracks caused by volume shrinkage during the hydration and hardening stage of concrete, cracks caused by uneven deformation of concrete structures due to temperature changes, cracks caused by external static and dynamic loads and stresses during service, called load cracks, and frost heave cracks caused by the freezing and expansion of water absorbed in concrete due to lower temperatures. The generation of these cracks will not only lead to a decrease in the mechanical properties of the concrete structure, but also a decrease in its waterproof and anti-seepage properties. Especially for concrete structures serving in marine, water conservancy and hydropower, tunnels and other projects, the generation of cracks will lead to accelerated erosion of the steel bars in the concrete structure, thereby accelerating the destruction of the concrete structure, and reducing its bearing capacity and durability.
[0004] Prevention and repair of cracks in concrete structures can help reduce the adverse effects. However, since many microcracks in concrete structures cannot be discovered in the early stages, and the timing of crack generation cannot be determined, traditional methods such as filling, grouting, and surface repair can only repair cracks that have been discovered and are relatively obvious, and cannot repair internal microcracks that are not easily discovered in a timely manner. Therefore, these traditional methods cannot effectively solve the hazards caused by cracks in concrete. Summary of the invention
[0005] In view of the above problems, the present invention provides a preparation process of a concrete crack self-healing repair agent and a concrete material thereof, wherein the repair agent has the function of repairing microcracks generated in the preparation stage of the concrete structure and microcracks generated during the service process, thereby reducing the damage caused to the concrete structure. Specifically, the technical solution of the present invention is as follows.
[0006] First, the present invention provides a preparation process of a concrete crack self-healing repair agent, comprising the following steps:
[0007] (1) Graphene oxide (GO) was ultrasonically dispersed in a saturated Mg 2+ The pretreatment solution is obtained by mixing the dispersed aqueous solution of the source.
[0008] (2) The γ-C2S and the pretreatment liquid are mixed evenly and then dried, and then an alkali solution is added to the obtained powder to form a mixed material, and the mixed material is calcined in a protective atmosphere. After completion, the mixed material is ground to obtain a repair agent precursor.
[0009] (3) The repair agent precursor is immersed in an ethanol solution of a silane coupling agent, and then dried to obtain a concrete crack self-healing repair agent (γ-C2S@MgO@GO) modified by a silane coupling agent.
[0010] Furthermore, in step (1), the content of graphene oxide in the dispersed aqueous solution is 1.5-3.2 g / L.
[0011] Furthermore, in step (1), the Mg 2+ The source includes at least one of magnesium sulfate, magnesium nitrate, magnesium gluconate, and the like.
[0012] Furthermore, in step (2), the ratio of γ-C2S to pretreatment liquid is 1 g: 0.8-1.1 ml. Optionally, the drying temperature is 70-100° C., and the drying time is 1-2 hours.
[0013] Furthermore, in step (2), the ratio of the powder to the alkali solution is 1 g: 0.5-0.7 ml. Optionally, the mass fraction of the alkali solution is 20-30%. The alkali solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution, potassium carbonate solution, etc.
[0014] Furthermore, in step (2), the calcination treatment is carried out at a temperature of 400-500° C. and for a time of 15-30 min.
[0015] Furthermore, in step (3), the ratio of the repair agent precursor to the ethanol solution of the silane coupling agent is 1 g: 5-10 ml. Optionally, the mass fraction of the silane coupling agent in the ethanol solution is 0.2-0.5%.
[0016] Furthermore, in step (3), the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane (KH-550), γ-glycidyloxypropyltrimethoxysilane (KH-560), γ-methacryloxypropyltrimethoxysilane (KH-570), N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane (DL602), etc.
[0017] Furthermore, in step (3), the immersion time is 20-30 minutes. Optionally, the drying temperature is 45-60°C and the drying time is 3-5 minutes.
[0018] Furthermore, in step (3), the fineness of the crack self-healing repair agent is 60-100 mesh.
[0019] Secondly, the present invention provides a crack self-healing concrete material, comprising the following components: 100-125 parts by weight of silicate cement, 220-270 parts by weight of coarse aggregate, 180-230 parts by weight of fine aggregate, 25-32 parts by weight of fly ash, 13-17 parts by weight of silica fume, 7-10 parts by weight of the above-mentioned crack self-healing repair agent, 4-6 parts by weight of modified calcium sulfoaluminate powder, 2-2.5 parts by weight of redispersible latex powder, 1.5-2.4 parts by weight of water reducer, and 45-58 parts by weight of mixing water.
[0020] Furthermore, the preparation method of the modified calcium sulphoaluminate powder comprises the following steps: mixing calcium sulphoaluminate powder, rubber powder and anhydrous ethanol containing a silane coupling agent, and then drying to obtain the modified calcium sulphoaluminate powder.
[0021] Furthermore, the ratio of the calcium sulfoaluminate powder, rubber powder and anhydrous ethanol is 1g: 0.2-0.25g: 0.4-0.6ml. Optionally, the fineness of the calcium sulfoaluminate powder is 100-120 mesh, and the fineness of the rubber powder is 200-300 mesh.
[0022] Furthermore, the mass fraction of the silane coupling agent in the anhydrous ethanol is 0.2-0.5%.
[0023] Optionally, the silane coupling agent includes at least one of γ-aminopropyltriethoxysilane (KH-550), γ-glycidyloxypropyltrimethoxysilane (KH-560), γ-methacryloxypropyltrimethoxysilane (KH-570), and the like.
[0024] Furthermore, the drying temperature is 70-85° C., and the modified calcium sulphoaluminate powder is obtained by drying at this temperature to a constant weight.
[0025] Furthermore, the redispersible latex powder includes at least one of ethylene-vinyl acetate copolymer latex powder (VAE), polyacrylate latex powder (PAE), and the like.
[0026] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:
[0027] The concrete crack self-healing repair agent prepared by the present invention contains γ-C2S and MgO, and is modified with a silane coupling agent. It can not only reduce cracks caused by volume shrinkage during the preparation stage of the concrete structure, but also automatically repair cracks generated in the concrete structure during the later service process, reducing the adverse effects on the mechanical properties and waterproof and anti-seepage properties of the concrete structure. After being added to the repair agent, the MgO therein undergoes a hydration reaction in the hydration and hardening stage of the concrete material to form magnesium hydroxide with volume expansion characteristics, which can compensate for the volume shrinkage of the concrete structure caused by water loss and reduce the tendency of cracks caused by volume shrinkage. At the same time, the silane coupling agent in the repair agent connects the formed magnesium hydroxide with the organic functional groups on the surface of the cement hydration product in the concrete structure and the polymer film formed by the redispersible latex powder, which can further reduce the tendency of cracks caused by volume shrinkage, thereby helping to reduce the number of cracks in the concrete. Since the hydration activity of γ-C2S is very low, after the above process, the crack self-healing repair agent is transformed into γ-C2S@Mg(OH)2@GO and distributed in the cured concrete structure. After microcracks are generated in the subsequent service process, the external moisture and carbon dioxide react with the γ-C2S on the crack fracture surface to form silica particles and calcium carbonate. The silica particles and Mg(OH)2 further undergo hydration reaction to form magnesium-silicon hydrated cementitious products (MSH). At the same time, the silica particles can also undergo secondary hydration reaction with the hydration product Ca(OH)2 in the concrete structure to form calcium hydrated cementitious products / hydrated calcium silicate (CSH). All of the above-mentioned cementitious products can bond and repair microcracks. At the same time, the GO doped in the repair agent in the cementitious product can effectively improve its crack resistance, and the calcium carbonate can compact the cementitious product, thereby improving the repair effect of cracks. In addition, the present invention also adds modified calcium sulfoaluminate powder to the concrete material. After adding the modified calcium sulfoaluminate powder to the concrete material, the calcium sulfoaluminate reacts with water to form a calcium sulfoaluminate hydrate gel product with micro-expansion characteristics, and the rubber powder is mixed in the calcium sulfoaluminate hydrate gel product to make it have good toughness. Therefore, it can not only effectively compensate for the volume shrinkage generated by the concrete structure in the hydration and hardening stage, but also absorb the internal stress generated by the volume shrinkage, reducing the generation of cracks. At the same time, the silane coupling agent on the modified calcium sulfoaluminate powder also helps to improve the bonding force between the calcium sulfoaluminate hydrate gel product and the concrete matrix, thereby improving the crack resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] It should be noted that the drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention and do not constitute an improper limitation of the present invention.
[0029] Figure 1This is a sample picture of the concrete crack self-healing repair agent prepared in the following Example 1.
[0030] Figure 2 This is a graph showing the compressive strength test of the concrete material prepared in the following Example 1.
[0031] Figure 3 The following is a test chart of the water seepage resistance of the concrete materials prepared in Examples 1 to 6. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. Unless otherwise defined, all professional and scientific terms used in the present invention have the same meaning as those familiar to those skilled in the art. The preferred implementation methods and materials described in the present invention are only for demonstration purposes. The reagents or raw materials used in the invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or are used according to the product specification. Now the technical scheme of the present invention is further described in conjunction with specific embodiments.
[0033] Example 1
[0034] 1. A preparation process of a concrete crack self-healing repair agent, comprising the following steps:
[0035] (1) Add graphene oxide to a saturated magnesium sulfate solution for ultrasonic dispersion to obtain a pretreatment solution having a graphene oxide content of 3 g / L for later use.
[0036] (2) The γ-C2S powder and the pretreatment liquid were mixed at a ratio of 1 g:0.9 ml and stirred evenly, then heated to 80°C and dried for 1 hour, and then the obtained powder was mixed with a 20% sodium hydroxide solution at a ratio of 1 g:0.6 ml and stirred evenly. The obtained mixture was heated to 450°C in a nitrogen atmosphere and calcined for 25 minutes, then cooled to room temperature, and the product was ground to obtain a repair agent precursor.
[0037] (3) The repair agent precursor is added to ethanol (mass fraction 92%) with a mass fraction of KH-550 of 0.4%, and the ratio of the two is 1g:7.5ml. After stirring evenly, the mixture is immersed for 20 minutes. After completion, the repair agent precursor is filtered out and dried at 50°C for 3 minutes. After sieving, a concrete crack self-healing repair agent with a fineness of 100 mesh is obtained (such as Figure 1 as shown), for standby use.
[0038] 2. A method for preparing modified calcium sulfoaluminate powder, comprising the following steps: mixing 120-mesh calcium sulfoaluminate powder, 300-mesh rubber powder and anhydrous ethanol containing 0.35 wt.% silane coupling agent (KH-550) in a ratio of 1 g: 0.22 g: 0.5 ml, stirring evenly, and then drying the mixed powder at 70°C to constant weight to obtain modified calcium sulfoaluminate powder.
[0039] 3. A method for preparing a crack self-healing concrete material, comprising the steps of:
[0040] Take the raw material components according to the following proportions: 110 parts by weight of 42.5 ordinary Portland cement, 240 parts by weight of crushed stone coarse aggregate with a particle size of 5-10 mm, 200 parts by weight of river sand fine aggregate with a particle size of 0.2-0.5 mm, 28 parts by weight of fly ash, 15 parts by weight of silica fume, 9.5 parts by weight of the crack self-healing repair agent of this embodiment, 5 parts by weight of the modified calcium sulfoaluminate powder of this embodiment, 2.2 parts by weight of ethylene-vinyl acetate copolymer latex powder, 1.8 parts by weight of polycarboxylate water reducer, and 52 parts by weight of mixing water. Mix the above components and stir evenly to obtain concrete material.
[0041] Performance test: (1) The compressive strength recovery rate of the concrete material prepared in this embodiment after self-repair of load damage was tested according to the method of "4.4 Concrete load damage self-repair test" in the "Standard for Test Methods for Self-repair Performance of Cement Concrete" (TCECS 913-2021). The compressive strength test is as follows: Figure 2 (2) The water-resistance performance of the concrete material prepared in this embodiment was tested according to the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GBT 50082-2009). Figure 3 As shown), the results are as follows: compressive strength recovery rate = 125.82%, water seepage height = 7.3mm.
[0042] Example 2
[0043] 1. A preparation process of a concrete crack self-healing repair agent, comprising the following steps:
[0044] (1) Add graphene oxide to a saturated magnesium nitrate solution for ultrasonic dispersion to obtain a pretreatment solution having a graphene oxide content of 1.5 g / L for later use.
[0045] (2) The γ-C2S powder and the pretreatment liquid were mixed at a ratio of 1 g:0.8 ml and stirred evenly, then heated to 70°C and dried for 2 hours, and then the obtained powder was mixed with a 20% sodium carbonate solution at a ratio of 1 g:0.5 ml and stirred evenly. The obtained mixture was heated to 400°C in a nitrogen atmosphere and calcined for 30 minutes, then cooled to room temperature, and the product was ground to obtain a repair agent precursor.
[0046] (3) Add the repair agent precursor to ethanol (mass fraction 92%) with a mass fraction of KH-560 of 0.2% in a ratio of 1 g:5 ml, stir evenly and soak for 25 minutes. After completion, filter out the repair agent precursor and dry it at 60°C for 3 minutes. After sieving, obtain a concrete crack self-healing repair agent with a fineness of 80 mesh for use.
[0047] 2. A method for preparing modified calcium sulfoaluminate powder, comprising the following steps: mixing 100-mesh calcium sulfoaluminate powder, 250-mesh rubber powder and anhydrous ethanol containing 0.2wt.% silane coupling agent (KH-560) in a ratio of 1g:0.25g:0.6ml, stirring evenly, and then drying the mixed powder at 80°C to constant weight to obtain modified calcium sulfoaluminate powder.
[0048] 3. A method for preparing a crack self-healing concrete material, comprising the steps of:
[0049] Take the raw material components according to the following proportions: 100 parts by weight of 42.5 ordinary Portland cement, 220 parts by weight of crushed stone coarse aggregate with a particle size of 5-10 mm, 180 parts by weight of river sand fine aggregate with a particle size of 0.2-0.5 mm, 25 parts by weight of fly ash, 13 parts by weight of silica fume, 7 parts by weight of the crack self-healing repair agent of this embodiment, 4 parts by weight of the modified calcium sulfoaluminate powder of this embodiment, 2 parts by weight of ethylene-vinyl acetate copolymer latex powder, 1.5 parts by weight of polycarboxylate water reducer, and 45 parts by weight of mixing water. Mix the above components and stir evenly to obtain concrete material.
[0050] The compressive strength recovery rate and water seepage resistance of the concrete material prepared in this embodiment were tested using the same method as in the above embodiment 1. Figure 3 As shown), the results are as follows: compressive strength recovery rate = 114.37%, water seepage height = 10.4mm.
[0051] Example 3
[0052] 1. A preparation process of a concrete crack self-healing repair agent, comprising the following steps:
[0053] (1) Add graphene oxide to a saturated magnesium nitrate solution for ultrasonic dispersion to obtain a pretreatment solution having a graphene oxide content of 3.2 g / L for later use.
[0054] (2) The γ-C2S powder and the pretreatment liquid were mixed at a ratio of 1 g:1.1 ml and stirred evenly, then heated to 100°C and dried for 1 hour, and then the obtained powder was mixed with a 30% by mass sodium hydroxide solution at a ratio of 1 g:0.7 ml and stirred evenly. The obtained mixture was heated to 500°C in a nitrogen atmosphere and calcined for 15 minutes, then cooled to room temperature, and the product was ground to obtain a repair agent precursor.
[0055] (3) Add the repair agent precursor to ethanol (mass fraction 90%) with a mass fraction of KH-570 of 0.5%, with the ratio of the two being 1g:10ml, stir evenly and soak for 30 minutes. After completion, filter out the repair agent precursor and dry it at 45°C for 5 minutes. After sieving, obtain a concrete crack self-healing repair agent with a fineness of 60 mesh, which is set aside.
[0056] 2. A method for preparing modified calcium sulfoaluminate powder, comprising the following steps: mixing 100-mesh calcium sulfoaluminate powder, 200-mesh rubber powder and anhydrous ethanol containing 0.5wt.% silane coupling agent (KH-570) in a ratio of 1g:0.2g:0.4ml, stirring evenly, and then drying the mixed powder at 85°C to constant weight to obtain modified calcium sulfoaluminate powder.
[0057] 3. A method for preparing a crack self-healing concrete material, comprising the steps of:
[0058] Take the raw material components according to the following proportions: 125 parts by weight of 42.5 ordinary Portland cement, 270 parts by weight of crushed stone coarse aggregate with a particle size of 5-10 mm, 230 parts by weight of river sand fine aggregate with a particle size of 0.2-0.5 mm, 32 parts by weight of fly ash, 17 parts by weight of silica fume, 10 parts by weight of the crack self-healing repair agent of this embodiment, 6 parts by weight of the modified calcium sulfoaluminate powder of this embodiment, 2.5 parts by weight of polyacrylate glue powder, 2.4 parts by weight of polycarboxylate water reducer, and 58 parts by weight of mixing water. Mix the above components and stir evenly to obtain concrete material.
[0059] The compressive strength recovery rate and water seepage resistance of the concrete material prepared in this embodiment were tested using the same method as in the above embodiment 1. Figure 3 As shown), the results are as follows: compressive strength recovery rate = 119.54%, water seepage height = 9.2mm.
[0060] Example 4
[0061] A preparation method of a crack self-healing concrete material comprises the following steps:
[0062] Take the raw material components according to the following proportions: 110 parts by weight of 42.5 ordinary Portland cement, 240 parts by weight of crushed stone coarse aggregate with a particle size of 5-10 mm, 200 parts by weight of river sand fine aggregate with a particle size of 0.2-0.5 mm, 28 parts by weight of fly ash, 15 parts by weight of silica fume, 2.2 parts by weight of ethylene-vinyl acetate copolymer latex powder, 1.8 parts by weight of polycarboxylate water reducer, and 52 parts by weight of mixing water. Mix the above components and stir evenly to obtain concrete material.
[0063] The compressive strength recovery rate and water seepage resistance of the concrete material prepared in this embodiment were tested using the same method as in the above embodiment 1. Figure 3 As shown), the results are as follows: compressive strength recovery rate = 32.18%, water seepage height = 23.6mm.
[0064] Example 5
[0065] A preparation process of a concrete crack self-healing repair agent, which is the same as the above-mentioned embodiment 3, except that the concrete crack self-healing repair agent of this embodiment is prepared by the following method:
[0066] (1) Add graphene oxide to water for ultrasonic dispersion to obtain a pretreatment solution having a graphene oxide content of 3.2 g / L for later use.
[0067] (2) The γ-C2S powder and the pretreatment liquid were mixed at a ratio of 1 g:1.1 ml and stirred evenly, then heated to 100°C and dried for 1 hour, and then the obtained powder was mixed with a 30% by mass sodium hydroxide solution at a ratio of 1 g:0.7 ml and stirred evenly. The obtained mixture was heated to 500°C in a nitrogen atmosphere and calcined for 15 minutes, then cooled to room temperature, and the product was ground to obtain a repair agent precursor.
[0068] (3) Add the repair agent precursor to ethanol (mass fraction 90%) with a mass fraction of KH-570 of 0.5%, with the ratio of the two being 1 g:10 ml, stir evenly and soak for 30 minutes. After completion, filter out the repair agent precursor and dry it at 45°C for 5 minutes. After sieving, obtain a concrete crack self-healing repair agent with a fineness of 60 mesh.
[0069] The compressive strength recovery rate and water seepage resistance of the concrete material prepared in this embodiment were tested using the same method as in the above embodiment 1. Figure 3 As shown), the results are as follows: compressive strength recovery rate = 86.07%, water seepage height = 14.2mm.
[0070] Example 6
[0071] A preparation process of a concrete crack self-healing repair agent, which is the same as the above-mentioned embodiment 2, except that the concrete crack self-healing repair agent of this embodiment is prepared by the following method:
[0072] (1) Add graphene oxide to a saturated magnesium nitrate solution for ultrasonic dispersion to obtain a pretreatment solution having a graphene oxide content of 1.5 g / L for later use.
[0073] (2) The γ-C2S powder and the pretreatment liquid were mixed at a ratio of 1 g:0.8 ml and stirred evenly, then heated to 70°C and dried for 2 hours, and then the obtained powder was mixed with a 20% sodium carbonate solution at a ratio of 1 g:0.5 ml and stirred evenly. The obtained mixture was heated to 400°C in a nitrogen atmosphere and calcined for 30 minutes, then cooled to room temperature, and the product was ground to obtain a repair agent precursor.
[0074] (3) Add the repair agent precursor to 92% ethanol in a ratio of 1 g:5 ml, stir evenly and soak for 25 min. After completion, filter out the repair agent precursor and dry it at 60 ° C for 3 min. After sieving, obtain a concrete crack self-healing repair agent with a fineness of 80 mesh.
[0075] The compressive strength recovery rate and water seepage resistance of the concrete material prepared in this embodiment were tested using the same method as in the above embodiment 1. Figure 3 As shown), the results are as follows: compressive strength recovery rate = 102.25%, water seepage height = 11.6mm.
[0076] Example 7
[0077] A preparation process of a concrete crack self-healing repair agent is the same as that of the above-mentioned embodiment 1, except that the modified calcium sulfoaluminate powder of this embodiment is prepared by the following method: 120-mesh calcium sulfoaluminate powder, 300-mesh rubber powder and anhydrous ethanol are mixed in a ratio of 1g:0.22g:0.5ml and stirred evenly, and then the mixed powder is dried at 70°C to constant weight to obtain the modified calcium sulfoaluminate powder.
[0078] The compressive strength recovery rate and water seepage resistance of the concrete material prepared in this embodiment were tested by the same method as in the above embodiment 1, and the results were as follows: compressive strength recovery rate = 98.04%, water seepage height = 10.8 mm.
[0079] Example 8
[0080] A preparation process of a concrete crack self-healing repair agent, which is the same as the above-mentioned embodiment 3, except that the concrete crack self-healing repair agent of this embodiment is prepared by the following method:
[0081] (1) γ-C2S powder and saturated magnesium nitrate solution were mixed at a ratio of 1 g:1.1 ml and stirred evenly, then heated to 100°C and dried for 1 hour, and then the obtained powder was mixed with 30% sodium hydroxide solution at a ratio of 1 g:0.7 ml and stirred evenly. The obtained mixture was heated to 500°C in a nitrogen atmosphere and calcined for 15 minutes, then cooled to room temperature, and the product was ground to obtain a repair agent precursor.
[0082] (2) Add the repair agent precursor to ethanol (mass fraction 90%) with a mass fraction of KH-570 of 0.5%, with the ratio of the two being 1 g:10 ml, stir evenly and soak for 30 minutes. After completion, filter out the repair agent precursor and dry it at 45°C for 5 minutes. After sieving, obtain a concrete crack self-healing repair agent with a fineness of 60 mesh.
[0083] The compressive strength recovery rate and water seepage resistance of the concrete material prepared in this embodiment were tested by the same method as in the above-mentioned embodiment 1, and the results were as follows: compressive strength recovery rate = 108.15%, water seepage height = 10.1 mm.
[0084] Example 9
[0085] A preparation process of a concrete crack self-healing repair agent is the same as that of Example 3, except that the modified calcium sulfoaluminate powder of this example is prepared by the following method: 100-mesh calcium sulfoaluminate powder and anhydrous ethanol containing 0.2wt.% silane coupling agent (KH-570) are mixed in a ratio of 1g:0.6ml and stirred evenly, and then the mixed powder is dried at 80°C to constant weight to obtain the modified calcium sulfoaluminate powder.
[0086] The compressive strength recovery rate and water seepage resistance of the concrete material prepared in this embodiment were tested by the same method as in the above embodiment 1, and the results were as follows: compressive strength recovery rate = 93.21%, water seepage height = 12.7 mm.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made shall be included in the protection scope of the present invention.
Claims
1. A preparation process of a concrete crack self-healing repair agent, characterized in that: The steps include: (1) Ultrasonic dispersion of graphene oxide in a saturated Mg 2+ The obtained pre-treatment solution is used for standby use, wherein the content of graphene oxide is 1.5-3.2 g / L; (2) γ-C2S and the pretreatment liquid are mixed in a ratio of 1g:0.8~1.1ml and then dried, and then alkali solution is added to the obtained powder to form a mixture, and the mixture is calcined in a protective atmosphere, and then ground to obtain a repair agent precursor; the ratio of the powder to the alkali solution is 1g:0.5~0.7ml; the mass fraction of the alkali solution is 20~30%; the temperature of the calcination treatment is 400~500℃, and the time is 15~30min; (3) The repair agent precursor is immersed in an ethanol solution of a silane coupling agent, and then dried to obtain the concrete crack self-healing repair agent; the ratio of the repair agent precursor to the ethanol solution of the silane coupling agent is 1g:5-10ml, and the mass fraction of the silane coupling agent in the ethanol solution is 0.2-0.5%.
2. The preparation process of the concrete crack self-healing repair agent according to claim 1, characterized in that: In step (1), the Mg 2+ The source includes at least one of magnesium sulfate, magnesium nitrate, and magnesium gluconate.
3. The preparation process of the concrete crack self-healing repair agent according to claim 1, characterized in that: In step (2), the drying temperature is 70-100° C. and the drying time is 1-2 hours.
4. The preparation process of the concrete crack self-healing repair agent according to claim 1, characterized in that: In step (2), the alkaline solution includes at least one of sodium hydroxide solution, potassium hydroxide solution, sodium carbonate solution and potassium carbonate solution.
5. The preparation process of the concrete crack self-healing repair agent according to any one of claims 1 to 4, characterized in that: In step (3), the silane coupling agent includes at least one of γ-aminopropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, and N-β-(aminoethyl)-γ-aminopropyl methyl dimethoxysilane; Alternatively, in step (3), the immersion time is 20 to 30 minutes; Alternatively, in step (3), the drying temperature is 45-60°C and the drying time is 3-5 min; Alternatively, in step (3), the fineness of the crack self-healing repair agent is 60-100 mesh.
6. A crack self-healing concrete material, characterized in that: The invention comprises the following components: 100-125 parts by weight of cement, 220-270 parts by weight of coarse aggregate, 180-230 parts by weight of fine aggregate, 25-32 parts by weight of fly ash, 13-17 parts by weight of silica fume, 7-10 parts by weight of the crack self-healing repair agent obtained by the preparation process according to any one of claims 1 to 5, 4-6 parts by weight of modified calcium sulfoaluminate powder, 2-2.5 parts by weight of redispersible latex powder, 1.5-2.4 parts by weight of water reducer and 45-58 parts by weight of mixing water.
7. The crack self-healing concrete material according to claim 6, characterized in that: The preparation method of the modified calcium sulphoaluminate powder comprises the following steps: mixing calcium sulphoaluminate powder, rubber powder and anhydrous ethanol containing a silane coupling agent, and then drying to obtain the modified calcium sulphoaluminate powder.
8. The crack self-healing concrete material according to claim 7, characterized in that: The ratio of calcium sulfoaluminate powder, rubber powder and anhydrous ethanol is 1g: 0.2-0.25g: 0.4-0.6ml; Alternatively, the fineness of the calcium sulphoaluminate powder is 100-120 mesh; Alternatively, the fineness of the rubber powder is 200-300 meshes.
9. The crack self-healing concrete material according to claim 7, characterized in that: The silane coupling agent includes at least one of KH-550, KH-560 and KH-570; Alternatively, the drying temperature is 70-85° C., and the mixture is dried at this temperature to a constant weight.
10. The crack self-healing concrete material according to any one of claims 6 to 9, characterized in that: The redispersible latex powder includes at least one of ethylene-vinyl acetate copolymer latex powder and polyacrylate latex powder.
Citation Information
Patent Citations
Reinforced concrete structure repairing material as well as preparation and use methods thereof
CN116023106A
Anti-abrasion ultra-high performance concrete and preparation method thereof
CN116477894A